On violence - "Arendt, Hannah" (London, 1970)
An analysis of the nature, causes, and significance of violence in the second half of the twentieth century. Arendt also re-examines the relationship between war, politics, violence, and power. AUTHOR: Hannah Arendt (1906-1975) taught political science and philosophy at the New School for Social Research in New York, Brooklyn College, and the University of Chicago. She also wrote political studies "Origins of Totalitarianism" 1951, "The Human Condition" 1958, "Eichmann in Jerusalem" 1963 REVIEWS: 'Incisive, deeply probing, written with clarity and grace, it provides an ideal framework for understanding the turbulence of our times' -
Keywords: Violence